Relationship Between Length and Curvature of Ascending Aorta and Type a Dissection - Sun, Lianjie; Li, Xiao; Wang, Guoqing; Sun, Jianchao; Zhang, Xiaoming; Chi, Honghui; Cao, Huihui; Ma, Wanteng; Yan, Zhisheng; Liu, Gaoli (Frontiers in Cardiovascular Medicine, 2022)
Background: Type A aortic dissection (TAAD) has a rapid onset and high mortality. Currently, aortic diameter is the major criterion for evaluating the risk of TAAD. We attempted to find other aortic morphological indicators to further analyze their relationships with the risk of type A dissection. Methods: We included the imaging and clinical data of 112 patients. The patients were divided into three groups, of which Group 1 had 49 patients with normal aortic diameter, Group 2 had 22 patients with ascending aortic aneurysm, and Group 3 had 41 patients with TAAD. We used AW Server software, version 3.2, to measure aorta-related morphological indicators. Results: First, in Group 1, the univariate analysis results showed that ascending aortic diameter was correlated with patient age (r2=0.35) and ascending aortic length (AAL) (r2=0.43). AAL was correlated with age (r2=0.12) and height (r2=0.11). Further analysis of the aortic morphological indicators among the three groups found that the median aortic diameter was 36.20 mm in Group 1 (Q1-Q3: 33.40-37.70 mm), 42.5 mm in Group 2 (Q1-Q3: 41.52-44.17 mm) and 48.6 mm in Group 3 (Q1-Q3: 42.4-55.3 mm). There was no significant difference between Groups 2 and 3 (P>0.05). Group 3 had the longest AAL (median: 109.4 mm, Q1-Q3: 118.3-105.3 mm), followed by Group 2 (median: 91.0 mm, Q1-Q3: 95.97-84.12 mm) and Group 1 (81.20 mm, Q1-Q3: 76.90-86.20 mm), and there were statistically significant differences among the three groups (P<0.05). The Aortic Bending Index (ABI) was 14.95 mm/cm in Group 3 (Q1-Q3: 14.42-15.78 mm/cm), 13.80 mm/cm in Group 2 (Q1-Q3: 13.42-14.42 mm/cm), and 13.29 mm/cm in Group 1 (Q1-Q3: 12.71-13.78 mm/cm), and the difference was statistically significant in comparisons between any two groups (P<0.05). Regression analysis showed that aortic diameter + AAL + ABI differentiated Group 2 and Group 3 with statistical significance (area under the curve (AUC)=0.834), which was better than aortic diameter alone (AUC=0.657) (P<0.05). Conclusions: We introduced the new concept of ABI, which has certain clinical significance in distinguishing patients with aortic dissection and aneurysm. Perhaps the ascending aortic dimeter combined with AAL and ABI could be helpful in preventing TAAD from occurring.